ANALISIS PENGUASAAN KATA SINONIM “TONGGUO”DAN “JINGGUO” PADA MAHASISWA ANGKATAN 2016 PENDIDIKAN BAHASA MANDARIN - Fatmawati Fatmawati; Lily Thamrin; Lusi Lusi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractSynonym is words that have the same meaning. In learning Chinese, there are many synonym words for example “tongguo” and “jingguo”.  Althought these two words have the same meaning, they have differences in their usage. Therefore, students who learn Chinese are often incorrect on using these two words. To find out how the conditions of mastery of Chinese Education Study Program FKIP UNTAN batch 2016 students on using the synonym of “tongguo” and “jingguo”, the writer used test method to find out the conditions of mastery of students and analyze the difficultiest of students on using the synonym of “tongguo” and “jingguo”. The results of the study stated that the mastery of students in the synonym word “tongguo” was better than the word “jingguo”. The percentage of correct answers “tongguo”reached 62% while the condition of students mastery of the synonym word “jingguo” only reached 52%.In the analysis of types of difficulties ,the writer realizes that the students mastered well on the use of the word “tongguo” shows success in a matter, while the use of the word “jingguo” shows the process of a thing. And students are not very mastery on the use of the word “tongguo” shows from one end or one point to the other end or one other point, while the use of the word “jingguo” shows passing  from a place.  Keywords: Synonym Word, Tongguo and Jingguo, The Condition of Mastery